(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A pot experiment was conducted in net house to study the effect of different rhizobial strains and N fertilizer on nodulation, growth, yield, N content and its uptake by soybean cv. Shohag. Saline soil was collected from Fultala of Khulna district. The experiment was laid out in the factorial combination following completely randomized design. There were altogether 16 treatment combinations (4 inocula × 4 fertilizer levels) replicated thrice. Four inocula viz., No strain, strain-102, strain-J43 and mixed strains (102 and J43) and four Levels of N viz., 0 (N0), 10 (N10), 15 (N15) and 20 (N20) kg N ha-1 were used. Both rhizobial strains and N alone or in combination significantly affected the nodulation, growth, yield, N content and its uptake by soybean. The highest values of most of the parameters were recorded from the plant inoculated with strain-J43 except the number of leaves plant-1. In case of N level, maximum values of all parameters were found when N was applied 15 kg ha-1 which was identical with N20. The treatment combination of strains-J43 and N15 showed best performance with respect to major parameters studied. The overall results thus suggest that rhizobial strains along with 15 kg N ha-1 can be used for producing higher yield and quality of soybean cv. Shohag in the salt affected soil. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22174 J. Environ. Sci. & Natural Resources, 7(1): 215-226 2014